Restoring Digital Ethics: Multilateral Efforts to Minimize the Erosion of Human Values in Cyberspace - Gina Aliyatul Jannah; Wisnu Adi Astra; Leondra Abiyu Abhinaya; Ismail Ismail; Nur Faizah; Nur Amalia Annisa; Arif Widagdo (Anthroposia: Journal of Social and Human Development, 2026)
The development of digital technology has transformed communication patterns, social interaction, and information dissemination in contemporary society. Although it provides significant benefits, digital transformation also generates ethical challenges such as misinformation, hate speech, cyberbullying, privacy violations, and declining communication ethics, which collectively contribute to the erosion of human values in cyberspace. These conditions indicate an imbalance between technological advancement and the strengthening of digital ethics and moral awareness among users. This study aims to analyze the forms of human value degradation in cyberspace and examine the roles of government, society, and educational institutions in restoring digital ethics through a multilateral approach. The study employs a qualitative literature review method based on academic journals, books, policy documents, and institutional reports. Data were analyzed using content analysis to identify and interpret key themes related to digital ethics restoration. The findings show that restoring digital ethics requires coordinated efforts among government regulation, societal participation, and educational reinforcement of digital literacy and character building to create a more responsible and human-centered digital ecosystem.